(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The last days of life the law is interpreted as the condition of an intentional person resulting from an injury or an incurable disease and a diagnosis by a physician according to the prognosis according to the medical standard. The condition inevitably leads to near-term death and includes permanent loss of function of the cerebral cortex that permanently lacks the ability to perceive and communicate. Without any behavioural responses that can be perceived there will be only automatic reactions. With medical knowledge, one could only use a tool to prolong life for a while before actually dyingin palliative care in terminally ill patients, near death, or patients who are desperate for treatment, such as cancer patients AIDS patients and other chronic diseases that nurses must have knowledge. Understanding the concepts of death and holistic near-death, which encompasses physical, mental, social and spiritual aspects, and has knowledge in many other relevant sciences and arts, including having knowledge and consideration of rights. And related laws as well as ethics in patient care.